Urinary excretion of gluten immunoreactive peptides as an indicator of gastrointestinal function after fasting and dietary provocation in healthy volunteers - Rodríguez-Ramírez, Raquel; Fernández Peralbo, María Auxiliadora; Mendía, Irati; Long, Joshua C. D.; Sousa, Carolina; Cebolla, Ángel (Frontiers in Immunology, 2024)
Introduction: Understanding intestinal permeability is paramount for elucidating gastrointestinal health and pathology. The size and nature of the molecule traversing the intestinal barrier offer crucial insights into various acute and chronic diseases, as well as the evolution of some conditions. This study aims to assess the urinary excretion kinetics of gluten immunogenic peptides (u-GIP), a unique class of dietary peptides detectable in urine, in volunteers under controlled dietary conditions. This evaluation will should be compared to established probes like lactulose, a human non-digestible disaccharide indicative of paracellular permeability, and mannitol, reflecting transcellular permeability. Methods: Fifteen participants underwent simultaneous ingestion of standardized doses of gluten (10 g), lactulose (10 g), and mannitol (1 g) under fasting conditions for at least 8 hours pre-ingestion and during 6 hours post-ingestion period. Urine samples were collected over specified time intervals. Excretion patterns were analyzed, and correlations between the lactulose-to-mannitol ratio (LMR) and u-GIP parameters were assessed. Results: The majority of u-GIP were detected within the first 12 hours post-ingestion. Analysis of the variability in cumulative excretion across two sample collection ranges demonstrated that lactulose and u-GIP exhibited similar onset and excretion dynamics, although GIP reached its maximum peak earlier than either lactulose or mannitol. Additionally, a moderate correlation was observed between the LMR and u-GIP parameters within the longest urine collection interval, indicating potential shared characteristics among permeability pathways. These findings suggest that extending urine collection beyond 6 hours may enhance data reliability.Discussion: This study sheds light on the temporal dynamics of u-GIP in comparison to lactulose and mannitol, established probes for assessing intestinal permeability. The resemblance between u-GIP and lactulose excretion patterns aligns with the anticipated paracellular permeability pathway. The capacity to detect antigenic food protein fragments in urine opens novel avenues for studying protein metabolism and monitoring pathologies related to the digestive and intestinal systems.